Agro-tourism Waste Processing Innovation with Vertical Composting in Harapan Farmer Group Palangka Raya - Fatiqin, Awalul; Alfanaar, Rokiy; Rahman, Sudarman; Norhusna, Norhusna; Dewi, Apriana; Hidayat, Muhamad Taufik; Febrianto, Yahya; Citrariana, Shesanti; Suprayogi, Thathit (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
Palangkaraya, with more than 500,000 hectares of peatland, faces major challenges in the management of its natural resources. Acidic and infertile peatlands require a special approach to increase agricultural productivity without damaging the environmental balance. One relevant approach is the application of the zero waste concept, where organic waste from agriculture and agro-tourism can be processed into high-quality compost. This community service program aims to introduce Organic Waste Composting Machine technology with Vertical Aerobic Composting method to Harapan Farmer Group in Palangkaraya. The program includes training in the use of technology and mentoring in organic waste management to improve peatland fertility. The results showed a significant increase in partners' understanding and skills in utilizing compost technology, and successfully supported the zero waste program by converting organic waste into useful compost. This program not only supports environmental sustainability, but also contributes to the improvement of partners' economic welfare through reduced dependence on chemical fertilizers.